2021
DOI: 10.52462/jlls.145
|View full text |Cite
|
Sign up to set email alerts
|

Foreign language teachers’ technological and pedagogical content knowledge: A study with AFL teachers in Indonesia

Abstract: Teaching-learning of the Arabic language has emerged as vital in both Muslim and non-Muslim countries. However, a lack of studies exists on measuring the technological pedagogical content knowledge (TPACK) of Arabic language teachers. Thus, this study explores Indonesian Arabic teachers' TPACK and provides a conceptualization that the elements of TPACK are not separate; rather, each element facilitates the sustenance of other elements. To achieve this objective, a quantitative research approach is undertaken u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…The results of the EFA revealed that four factors represent different aspects of Arabic language proficiency among teachers, as measured in this study. These factors are Arabic language teachers' knowledge of grammar (Nahwu), word forms (Shorof ), rhetoric (Balaghah), and vocabulary (Mu'jajamiyah), which are important components in assessing their knowledge [25,26]. The factor analysis results indicated that their knowledge of word structure, grammar rules, root words, rhetorical figures, and appropriate word usage in context all play significant roles as main components of Arabic language teachers' knowledge content.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the EFA revealed that four factors represent different aspects of Arabic language proficiency among teachers, as measured in this study. These factors are Arabic language teachers' knowledge of grammar (Nahwu), word forms (Shorof ), rhetoric (Balaghah), and vocabulary (Mu'jajamiyah), which are important components in assessing their knowledge [25,26]. The factor analysis results indicated that their knowledge of word structure, grammar rules, root words, rhetorical figures, and appropriate word usage in context all play significant roles as main components of Arabic language teachers' knowledge content.…”
Section: Discussionmentioning
confidence: 99%
“…Type of Research Amount References 1 Quantitative 10 (Al Musawi et al, 2016;Aladdin, 2013;Daif-Allah & Al-Sultan, 2023;Ishtaiwa & Shana, 2011;Ma'mun et al, 2021;Mingazova et al, 2020;Musthofa, 2022;Saifee et al, 2012;Yun, 2018;Zailani et al, 2014) 2 Qualitative 9 (Akmaliyah et al, 2021;Al-Dajani, 2019;Andrian & Yul, 2023;Baldwin, 2018;Eldin, 2015;Farzaneh, 2014;Fattakhova, 2015;Soliman & Khalil, 2022;Taha-Thomure, 2008) 3 Case study 2 (Amri et al, 2019;Columbu, 2021)…”
Section: Nomentioning
confidence: 99%
“…No Important information for each reference Formulation 1 Teaching Arabic and understanding it is very important for the sustainability of life (Saifee et al, 2012), continuity of the Arabic linguistic tradition (Fattakhova, 2015), for Muslim society (Farzaneh, 2014), and even non-Muslims (Ma'mun et al, 2021). Therefore, a moderate positive attitude towards the Arabic language is needed (Aladdin, 2013).…”
Section: Table 3 Important Information For Each Articlementioning
confidence: 99%
“…Good digital skills related to the search for evidence in bibliographies or specialized sites, selection, storage, evaluation of information and support of proposals for changes are perceived. [43] x x Quantitative Questionnaire Interview 130 students Universities need to focus on teaching and evaluating innovation competence. [46] x x x x Quantitative Descriptive Correlational…”
Section: Higher Education Teachersmentioning
confidence: 99%
“…On the other hand, teaching competencies allow the promotion of sustainable development through methods such as deliberative dialogue, problem-based learning, planning and project management [49]. That is why the development of studies that allow exploring the roles and pedagogical practices is recommended, which allows the development of teaching skills in teaching [43]. Nevertheless, it should be noted that the pedagogical perspective is related to curricular planning, diagnosis of students' learning needs, adaptation of lesson plans according to the student, planning of didactic strategies, planning of practical activities, planning of study visits, and experiments among others [27], [31], [35], [40], [49].…”
Section: Pedagogical Competencementioning
confidence: 99%